Effect of Beetroot on Hemoglobin Level in Pregnant Women: a Systematic Review - Kusmayra Ambarwati; Fitria Sari; Asyifa Robiatul Adawiyah; Yuna Trisuci Aprillia; Atik Kridawati (Science Tech Group, 2026)
Background: Anemia is a very large public health problem all over the world during pregnancy, and is a component of maternal and fetal morbidity. Recently, attention has focused on certain natural-source nutrients with high iron or folate content, such as beetroot (Beta vulgaris L.), as potential therapies for anemia in pregnant women. Purpose: The purpose of this systematic review was to investigate the impact of beetroot supplementation on hemoglobin levels in pregnant women. Methods: The original review was carried out based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guideline. Library searches were performed with PubMed, Scopus, Web of Science, and Google Scholar. The Population, Intervention, Comparison, and Outcome framework was used to develop the review question. Results: Of the identified studies, 19 were included. The majority of studies utilized experimental, quasi-experimental, or randomized controlled trial (RCT) designs; Indonesia is the country where most of the studies were carried out. The interventions primarily were beetroot juice, beet powder, and/or iron supplementation. The results were quite consistent, showing that beetroot supplementation effectively enhances hemoglobin levels in pregnant women with anemia. Improvements in the hematocrit and erythrocyte counts were also reported in several studies. Conclusions: Beetroot appears to be a nutrient-based remedy to consider alongside other nutritional therapies for managing anemia in pregnancy. But more rigorous randomized controlled trials with improved design, larger sample sizes, and standardized intervention protocols are needed.